Indications, complications, and early postoperative course of recovery of intraocular lens exchange xurgery: a Single-Center Retrospective Study = Indikationen, Komplikationen und früher postoperativer Erholungsverlauf nach Intraokularlinsen-Austausch : eine monozentrische retrospektive Studie - Silva, Marcio; Orguel, Selim; Becker, Matthias D.; Freiberg, Florentina Joyce (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To analyze the indications, complications, and early course of recovery of intraocular lens (IOL) exchange surgery. Material and Methods Records of patients who underwent IOL exchange during a 6-year period at a tertiary referral center were reviewed and the indications and complications after surgical intervention were analyzed. Their effects on postoperative corrected distance visual acuity (CDVA), intraocular pressure (IOP), use of IOP-lowering medications, and refractive cylindrical power were assessed. Results One hundred and seventy-one eyes (165 patients) were investigated. The most frequent indication for IOL exchange was lens dislocation in 163 eyes (95.32%). The main causes of IOL dislocation were pseudoexfoliation syndrome (PEX) in 98 eyes (57.31%) and complications during cataract surgery in 40 eyes (23.39%). During IOL exchange, an anterior iris-claw fixation was performed in 159 eyes (92.98%). After significant initial deterioration to 1.59 ± 1.08 logMAR on postoperative day 1 (p ≤ 0.001), the CDVA recovered to preoperative levels within 28 days. A significant decrease in IOP was observed on postoperative day 1 (p = 0.04). The most common postoperative complications were corneal edema in 114 eyes (66.67%) and vitreous hemorrhage in 67 eyes (39.18%). Conclusion The high early postoperative prevalence of corneal edema and intraocular hemorrhage was found to affect visual recovery after IOL exchange, causing a significant initial deterioration of CDVA and a delay of full visual recovery. These findings suggest that surgical approaches minimizing the risk of this type of complications should be favored.
Gesehen am 20.07.2023